Lipidomics reveals the potential mechanism of honokiol against adenine-induced chronic kidney disease - Liu, Xinhui; Gao, Liwen; Huang, Xi; Deng, Ruyu; Wei, Xian; Lu, Jiandong; Li, Shunmin (Frontiers in Pharmacology, 2022)
Honokiol (HKL), a biphenolic compound, is derived from the bark of Magnolia officinalis, which is used in traditional Chinese medicine for gastrointestinal complaints. HKL has diverse pharmacological activities and has protective effects in various disease models. However, the role and mechanism of HKL in treating chronic kidney disease (CKD) remain to be clarified. This study was designed to investigate whether HKL can alleviate CKD and its potential mechanism. Male Sprague-Dawley rats were fed 0.75% w/w adenine feed for 3 weeks to induce CKD. HKL was administrated by gavage at a dose of 5 mg/kg/day for 4 weeks. Using a special kit, serum creatinine (Scr) and blood urea nitrogen (BUN) were measured. To assess renal pathology, periodic acid-Schiff and Masson's trichrome staining were conducted. Renal lipid profiles were analyzed by ultra high performance liquid chromatography/mass spectrometry (UHPLC/MS). The results showed that administration of HKL reduced Scr and BUN, alleviated renal tubular atrophy and tubulointerstitial fibrosis in adenine-induced CKD rat model. By using lipidomics, we identified 113 lipids (47 lipids in negative ion mode, 66 lipids in positive ion mode) that could be significantly reversed by HKL treatment in CKD rats' kidneys. Most of these lipids belong to the phosphatidylcholine (PC), ceramide (Cer), phosphatidylethanolamine (PE), and triacylglycerol (TAG) classes. Moreover, HKL improved fatty acid oxidation in the kidney of CKD rats. In conclusion, this study found that HKL could protect against CKD induced by adenine, possibly through regulation of lipid metabolism.